Chemical tools to define and manipulate interferon-inducible Ubl protease USP18 - Griffin J. Davis; Anthony O. Omole; Yejin Jung; Wioletta Rut; Ronald Holewinski; Kiall F. Suazo; Hong-Rae Kim; Mo Yang; Thorkell Andresson; Marcin Drag; Euna Yoo (Nature Communications)
Abstract Ubiquitin-specific protease 18 (USP18) is a multifunctional cysteine protease primarily responsible for deconjugating the interferon-inducible ubiquitin-like modifier ISG15 from protein substrates. Here, we report the design and synthesis of activity-based probes (ABPs) that incorporate unnatural amino acids into the C-terminal tail of ISG15, enabling the selective detection of USP18 activity over other ISG15 cross-reactive deubiquitinases (DUBs) such as USP5 and USP14. Combined with a ubiquitin-based DUB ABP, the USP18 ABP is employed in a chemoproteomics screening platform to identify and assess inhibitors of DUBs including USP18. We further demonstrate that USP18 ABPs can be utilized to profile differential activities of USP18 in lung cancer cell lines, providing a strategy that will help define the activity-related landscape of USP18 in different disease states and unravel important (de)ISGylation-dependent biological processes.